2008
DOI: 10.1007/s12298-008-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina nitrate-assimilating enzymes (NR, NiR, GS) have higher specific activities and are more stable than those of rice

Abstract: Spirulina platensis, a cyanobacterium whose N-metabolic pathway is similar to that of higher plants like rice (Oryza sativa), produces tenfold more protein, indicating a higher capacity for nitrate utilization/removal. Our in vitro analyses in crude extracts revealed that this can be attributed, at least in part, to the higher specific activities (3-6 fold) and half lives (1.2-4.4 fold) of the N-assimilating enzymes, nitrate reductase (NR), nitrite reductase (NiR) and glutamine synthetase (GS) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Our earlier studies have shown that NR in Spirulina is substrate-inducible (Jha et al, 2007), a fact well known in higher plants but not in non-nitrogenfixing, nitrate-dependent cyanobacteria. We also showed that NR, NiR and GS in Spirulina have higher specific activities and stabilities at room temperature than those from rice (Ali et al, 2008). The present study was aimed at examining the thermotolerance of NR, NiR and GS in vitro in Spirulina, compared to those of rice, since higher plants are traditional sources for these enzymes.…”
Section: Short Communicationmentioning
confidence: 93%
See 4 more Smart Citations
“…Our earlier studies have shown that NR in Spirulina is substrate-inducible (Jha et al, 2007), a fact well known in higher plants but not in non-nitrogenfixing, nitrate-dependent cyanobacteria. We also showed that NR, NiR and GS in Spirulina have higher specific activities and stabilities at room temperature than those from rice (Ali et al, 2008). The present study was aimed at examining the thermotolerance of NR, NiR and GS in vitro in Spirulina, compared to those of rice, since higher plants are traditional sources for these enzymes.…”
Section: Short Communicationmentioning
confidence: 93%
“…Panvel 1) were obtained as described earlier (Ali et al, 2008), surface-sterilized, imbibed in distilled water and grown on washed wet cotton in plastic trays at 28 °C and 80 % humidity under white light (1 Klux, 12 hour diurnal cycle) for 9 days. Excised leaves were floated on 40 mM KNO 3 for 6 hrs, frozen in liquid N 2 and stored at -70 °C till use.…”
Section: Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations